Nitrogen and boron fertilization in cauliflower - Bonetti, J. A.; Fernandes, S. O.; Zanuzo, M. R.; Lange, A.; Machado, R. A. F. (Scientific Electronic Archives, 2021)
Nitrogen and boron participate concurrently in the growth and development process of plants by changingÂ Â cell division processes. Therefore, the aim of this study was to evaluate the influence of sources and doses of nitrogen, associated with boron doses and sulfur on the yield and quality aspects of Verona CMS cauliflower. The experimental design was set up under split plot design in randomized blocks, with 3 replicates. The treatments in the plot were sources of ammonium sulphate (NH4)2SO4) and calcium nitrate (Ca(NO3)2) x doses of nitrogen, being 125, 150, 175 and 200 kg ha-1 on topdressing system and in the subplot doses of boron (0, 2, 4 and 6 kg ha-1). The fresh curd mass, curd and stem diameter, total and commercial yield, besides the contents of nitrogen, boron and sulfur in the leaf and curd, were evaluated. The sources and doses of nitrogen and the doses of boron did not influence the fresh curd mass, stem diameter and the total yield of ’Verona CMS’ cauliflower. Enhancing doses of Ca(NO3)2 increased curd diameter, however in combination with boron doses there was antagonism effect on curd development. The contents of nitrogen and boron in the leaf were influenced by the fertilization of nitrogen and boron, respectively, when the calcium nitrate source was used.